Pressure induced structural and spin state transitions in Sr3Fe2O5. Issue 96 (3rd October 2016) - Xu, Yuanhui; Hao, Xianfeng; Liu, Shanshan; Wang, Jing; Shi, Chunxiang; Gao, Faming; Liu, Yongshan
Abstract : The effect of pressure on the structural, electronic and magnetic properties of the two-legged spin ladder structure Sr3 Fe2 O5 was investigated, using density functional theory within the generalized gradient approximation (GGA) + U method. Abstract : We report on a first-principles study of the effect of pressure on the structural, electronic and magnetic properties of the two-legged spin ladder structure Sr3 Fe2 O5, using density functional theory within the generalized gradient approximation (GGA)+ U method. The theoretical results showed that a first order structural transition with the space-group change from Immm to Ammm is found around 33 GPa, which is in fair agreement with the experimental value (30 GPa). Furthermore, a spin state cross from the high spin state ( S = 2) to the intermediate spin state ( S = 1) has been demonstrated in the four-fold square-planar FeO4 coordination, when further pressure is applied. The spin collapse is accompanied by a magnetic configuration transition (antiferromagnetic to ferromagnetic) and an electronic transition (insulating to metallic). However, the predicted pressure for spin state transition is considerably larger than the experimental value. The reason for this discrepancy originates from the constant Hubbard U value we adopted. Furthermore, the transition mechanism underlined has been uncovered in terms of density of states analysis and the evolution of the lattice parameters under the pressure.